GROWTH PERFORMANCE AND CARCASS PRODUCTION OF REX RABBITS FED WITH CORN OIL SUPPLEMENTATION - Agustin Pratiwi; Supadmo Supadmo; Andriyani Astuti; Panjono Panjono (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
This study was aimed to observe the growth performance and carcass production of male Rex rabbits fed with corn oil supplementation. Twenty four head of rabbits with 1.362±260 g initial body weight were randomly divided into four groups e.g. R0 (control), R1 (supplemented with 2% of corn oil supplementation), R2 (supplemented with 4% of corn oil supplementation), and R3 (supplemented with 6% of corn oil supplementation). Feed and water were offered ad libitum. The animals were raised for 56 days prior to slaughtering. The collected data was analyzed using one way analysis of variance and followed with least significant different analysis. Dry matter (DM), crude protein (CP), crude fiber (CF), and total digestible nutrient (TDN) intake of R3 was lower (P<0.05) than R0, R1, and R2. There were no significant differences among groups in average daily gain, feed convertion ratio, carcass percentage and meat bone ratio. It is concluded that supplementation of corn oil in the diet had no effect on growth performance and carcass production of Rex rabbits.